2021
DOI: 10.1111/pace.14289
|View full text |Cite
|
Sign up to set email alerts
|

Brady‐arrhythmias in patients with atrial fibrillation and heart failure of reduced ejection fraction: is his‐bundle pacing superior to biventricular pacing?

Abstract: Objective To investigate the efficacy and safety of His‐bundle pacing (HBP) compared with the traditional biventricular pacing (BVP) on patients with brady‐arrhythmias, who suffer from permanent atrial fibrillation (AF) and heart failure with reduced ejection fraction (HFrEF). Methods All patients with brady‐arrhythmias, permanent AF and HFrEF were continuously enrolled from January 2017 to July 2019 and followed up for at least 12 months. The differences in QRS duration (QRSd), New York Heart Association (NYH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…We systematically assessed studies on HBP with an assessment of TR, which comprised of 9 original research articles and 1 case series reporting nearly 5 years of experience from 546 patients across centers around the world (Grieco et al, 2021 ; Hasumi et al, 2018 ; Hu et al, 2020 ; Hu et al, 2021 ; Huang et al, 2019 ; Ma et al, 2021 ; Shan et al, 2018 ; Vijayaraman et al, 2017 ; Wu et al, 2021 ; Ye et al, 2021 ). This is the first systematic analysis of a patient cohort to demonstrate the incidence of TR with HBP and its quantification before and after the procedural follow‐up, demonstrating its effects on ventricular synchrony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We systematically assessed studies on HBP with an assessment of TR, which comprised of 9 original research articles and 1 case series reporting nearly 5 years of experience from 546 patients across centers around the world (Grieco et al, 2021 ; Hasumi et al, 2018 ; Hu et al, 2020 ; Hu et al, 2021 ; Huang et al, 2019 ; Ma et al, 2021 ; Shan et al, 2018 ; Vijayaraman et al, 2017 ; Wu et al, 2021 ; Ye et al, 2021 ). This is the first systematic analysis of a patient cohort to demonstrate the incidence of TR with HBP and its quantification before and after the procedural follow‐up, demonstrating its effects on ventricular synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…HBP can also normalize conduction in patients with bundle branch block (BBB), hence, it has a role as an alternative to CRT (Abdelrahman et al, 2018 ). As HBP lead can be implanted above tricuspid annulus, its effect on TV morphology is minimal, leading to reversal of TR (Grieco et al, 2021 ; Hasumi et al, 2018 ; Hu et al, 2020 ; Hu et al, 2021 ; Huang et al, 2019 ; Ma et al, 2021 ; Shan et al, 2018 ; Vijayaraman et al, 2017 ; Wu et al, 2021 ; Ye et al, 2021 ). In this systematic review, we provide an association of TR in patients undergoing HBP.…”
Section: Introductionmentioning
confidence: 99%
“…1), and 88 records were left after exclusion of duplications. Of these, by screening via title and abstract, 67 articles were subsequently excluded, and 12 studies (14,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) were included in this meta-analysis after further excluding single-arm studies, study protocols, and studies with irrelevant outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
“…Patients who received HPSP (LBBaP or HBP) and BVP were generally frequency-matched on age and sex (Table 1), period of the follow up were six months in seven studies, 12 months in two studies, 14 months, 18 months and 24 months in one study each. All patients have HF and CRT indication in 12 studies (14,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In seven studies (28-32, 34, 35), the majority of the subjects had non-ischemic cardiomyopathy (73%, n = 326).…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
“…[9][10][11] Cardiac conduction system pacing (CSP) involves direct stimulation of the conduction system distal to the level of block, thereby achieving normal activation of one or both ventricles. The beststudied modality is His-bundle pacing (HBP), first demonstrated clinically by Deshmukh et al 12 HBP has been shown to be a viable alternative in patients eligible for BiVP, [13][14][15][16] but is limited by problems such as high pacing thresholds, low sensed R waves, atrial over-sensing, and relatively lower success rates. 14,17 A more recent modality is left-bundle-area pacing (LBAP), first demonstrated by Huang et al, 18 which involves direct stimulation of the fascicles of the left bundle branch distal to site of block via transseptal lead placement.…”
Section: Introductionmentioning
confidence: 99%